2010
DOI: 10.1108/02683941011013849
|View full text |Cite
|
Sign up to set email alerts
|

Psychological contract and its motivational and health‐enhancing properties

Abstract: PurposeIt has been hypothesized that perceived contract fulfilment is positively associated with affective commitment, leading also to reduced turnover intentions, and with mental health, and that these relationships are fully mediated by work engagement. Employing the job demands resources (JDR) model, the purpose of this study is to examine the motivational and health‐enhancing properties driven by perceived employer psychological contact fulfilment.Design/methodology/approachThe hypotheses were tested in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
112
1
10

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(128 citation statements)
references
References 46 publications
5
112
1
10
Order By: Relevance
“…Employees tend to give something back to the employer and will therefore show more commitment in case of contract fulfilment. Besides, the research shows that Finnish employees have a better mental health in case of contract fulfilment (Parzefall and Hakanen, 2010). Finally, the research shows that engagement fully mediates the relation between mental health, employee motivation and the fulfilment of the psychological contract.…”
Section: Narrative Literature Review: Relationship Between the Psychomentioning
confidence: 88%
See 3 more Smart Citations
“…Employees tend to give something back to the employer and will therefore show more commitment in case of contract fulfilment. Besides, the research shows that Finnish employees have a better mental health in case of contract fulfilment (Parzefall and Hakanen, 2010). Finally, the research shows that engagement fully mediates the relation between mental health, employee motivation and the fulfilment of the psychological contract.…”
Section: Narrative Literature Review: Relationship Between the Psychomentioning
confidence: 88%
“…Finally, the research shows that engagement fully mediates the relation between mental health, employee motivation and the fulfilment of the psychological contract. The research also established that engagement plays an important mediating role in the psychological contract and several positive outcomes (Parzefall and Hakanen, 2010).…”
Section: Narrative Literature Review: Relationship Between the Psychomentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies have even found positive associations between engagement and health (e.g., Hallberg & Schaufeli, 2006;Schaufeli, Taris, & Van Rhenen, 2008). For instance, Parzefall and Hakanen (2010) found support for both a motivational as well as a health-enhancing process in which engagement fully mediated the impact that psychological contract fulfillment had on mental health. Therefore, although engagement is still a fairly new construct in I/O psychology, empirical findings revealing its positive relationship with performance and other positive outcomes in the workplace are reason enough to see why researchers and practitioners have developed an interest in its nomological network in research and application to the workplace.…”
Section: The Importance Of Engagementmentioning
confidence: 99%